K. T. Achaya: A Historical Dictionary of Indian Food - Saberi, Helen J (Petits Propos Culinaires, 1998)
K. T. Achaya: A Historical Dictionary of Indian Food: New Delhi, Oxford University Press, 1998: ISBN 0 19 564254 6: 347 pp, references, indexes, h/b, 35.00.